Enacting whole‐school relationships and sexuality education in England: Context matters. (30th March 2022) - Bragg, Sara; Ponsford, Ruth; Meiksin, Rebecca; Lohan, Maria; Melendez‐Torres, G.J.; Hadley, Alison; Young, Honor; Anne Barter, Christine; Taylor, Bruce; Bonell, Chris
Abstract: Evidence from intervention evaluations suggests that achieving meaningful and lasting social, behavioural and attitudinal change from relationships, sex and health education (RSHE) in schools requires more than just a curriculum. Whole‐school approaches appear particularly promising since they work at multiple levels. For instance, they may: engage with carers, communities and local services; address iniquitous cultures and norms; change school policies and practices; and actively involve young people themselves. They have also been advocated to tackle sexual harassment and abuse in schools. Currently, however, such approaches have not been rigorously evaluated in the UK. This article focuses on the whole‐school elements of two recent RSHE pilot studies conducted in English secondary schools. We describe how these elements were variably enacted in different settings. We analyse contextual factors that help account for these differences, including: teacher and departmental professional identity and autonomy; broader education policy including high‐stakes testing and school inspection judgements; the significance of support staff; and staff–student relationships and partnerships. We argue that the likely impact of whole‐school approaches and RSHE in schools more generally will depend on attending to all of these factors. The paper contributes firstly to debates about the theory and practice of RSHE by highlighting the significance of processes and cultures beyond the classroom in enabling or constraining positive change. Secondly it contributes to scholarship that elucidates the role of contexts, broadly defined, in understanding the enactment of policy and practice.